14 MeV calibration of JET neutron detectors—phase 1: calibration and characterization of the neutron source. (21st December 2017) - Batistoni, P.; Popovichev, S.; Cufar, A.; Ghani, Z.; Giacomelli, L.; Jednorog, S.; Klix, A.; Lilley, S.; Laszynska, E.; Loreti, S.; Packer, L.; Peacock, A.; et al.
Abstract: In view of the planned DT operations at JET, a calibration of the JET neutron monitors at 14 MeV neutron energy is needed using a 14 MeV neutron generator deployed inside the vacuum vessel by the JET remote handling system. The target accuracy of this calibration is  ±10% as also required by ITER, where a precise neutron yield measurement is important, e.g. for tritium accountancy. To achieve this accuracy, the 14 MeV neutron generator selected as the calibration source has been fully characterised and calibrated prior to the in-vessel calibration of the JET monitors. This paper describes the measurements performed using different types of neutron detectors, spectrometers, calibrated long counters and activation foils which allowed us to obtain the neutron emission rate and the anisotropy of the neutron generator, i.e. the neutron flux and energy spectrum dependence on emission angle, and to derive the absolute emission rate in 4 π sr. The use of high resolution diamond spectrometers made it possible to resolve the complex features of the neutron energy spectra resulting from the mixed D/T beam ions reacting with the D/T nuclei present in the neutron generator target. As the neutron generator is not a stable neutron source, several monitoring detectors were attached to it by means of an ad hoc mechanical structure to continuously monitor the neutron emission rate during the in-vessel calibration. These monitoring detectors, two diamond diodes and activation foils, have been calibrated in terms of neutrons/counts within  ±5% total uncertainty. A neutron source routine has been developed, able to produce the neutron spectra resulting from all possible reactions occurring with the D/T ions in the beam impinging on the Ti D/T target. The neutron energy spectra calculated by combining the source routine with a MCNP model of the neutron generator have been validated by the measurements. These numerical tools will be key in analysing the results from the in-vessel calibration and to derive the response of the JET neutron detectors to DT plasma neutrons starting from the response to the generator neutrons, and taking into account all the calibration circumstances.